Career Planning and Soft Skills - D, Swamy (IJRDO -Journal of Computer Science Engineering, 2016)
An attempt has been made in this paper to describe the details about competitive examinations and the following personality test including personal interview covering the criteria used. The Career planning is the first step the candidates have to do. Different ways of collecting career information include reading, talking and job shadowing. Strengthening reading comprehension is an important step in the process of preparing for examination. An attempt has been made to list the steps for this process. Communication skills both written and oral play a vital role in the process of selection. The author gives a detailed account of different types of communication skills and stresses the need for developing confidence by adequate preparation, knowledge of examination pattern and adoption good study process are important steps for success.